Characterization of mechanical and thermal properties of 100% recycled 3D printed ABS samples - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Sharum, Mohamad Afiq; Arep @ Ariff, Hambali (Penerbit Universiti Kebangsaan Malaysia, 2025)
Additive manufacturing enables rapid and cost-effective production of prototypes and final products, with Fused Deposition Modeling (FDM) being widely used due to its accessibility and low material costs. This study addresses a key research gap by analyzing the mechanical and thermal properties of 100% recycled ABS printed using an open-source FDM 3D printer. Unlike prior research focusing on blended materials or reinforcement techniques, this study evaluates the standalone performance of recycled ABS, offering insights into its viability for sustainable manufacturing. Recycled ABS filament was produced through mechanical recycling and used to fabricate test samples. Microstructural analysis of fractured samples in X, Y, and Z orientations revealed voids and pores in recycled ABS, while standard ABS exhibited air bubbles in specific orientations. Impact testing per ASTM D256 showed that recycled ABS had an impact strength of 154.67 J/m, significantly lower than the 383.31 J/m of standard ABS. Differential Scanning Calorimetry analysis indicated a glass transition temperature (Tg) of 100.14°C for recycled ABS, compared to 104.97°C for standard ABS, demonstrating relative thermal stability. While 100% recycled ABS exhibits reduced mechanical properties and impact strength, its thermal performance remains stable. This study comprehensively evaluates recycled ABS filament for FDM printing, highlighting its potential for sustainable manufacturing by minimizing material waste. The findings contribute valuable data on the feasibility of upcycling polymer waste for functional 3D-printed products, offering insights into the challenges and opportunities of integrating recycled ABS in green additive manufacturing.